Soviet and revolutionary developments in the countries of Central and Eastern Europe (1917–1923 years) - Ovcharenko, O. (Вісник Черкаського університету. Серія: Історичні науки, 2018)
Abstract The article discusses some aspects of the policy of the party and state leadership of the Soviet state – Soviet export revolution based on the idea of world revolution, which was one of the elements of revolutionary geopolitics. It is shown that in this context revolutions in Europe, especially in its central and eastern parts (Germany, Hungary, Poland and others.) took on special significance. The situation in these countries is estimated as quite good for further revolutionizing revolutions and other European regions. Because they were the main vectors of geopolitical interests of the Bolsheviks. It was shown to stimulate basic forms of Soviet Russia the revolutionary process and revolutionary crisis in the West: to promote the creation of communist parties, trips to organize revolutionary propaganda and revolutionary actions of the Bolshevik emissaries, military experts, advisors, significant financial and economic assistance and more. It is noted that the fall of the Soviet republics in Germany and Hungary gave rise to doubts about the success of communist revolutions in Europe. The new surge of hope was associated with an attempt in 1920 «Sovietization» of Poland by force of arms. Plans for organizing revolutionary actions of the Soviet leadership at the time harbored in countries like Czechoslovakia, Italy, Yugoslavia, Bulgaria. The defeat of the Polish campaign of the Red Army offensive intentions not cooled Bolsheviks. Only the failure of adventurous attempts to seize power in Germany (organization «German October») in autumn 1923, prepared by the leaders of the RCP (B), Comintern and the CPN, forced them to abandon the policy of the organization directly «storming the bastions of capitalism».